Effects of sodium hydroxide treatment of dried distillers' grains on digestibility, ruminal metabolism, and metabolic acidosis of feedlot steers - Freitas, T. B. (2016)
The objectives were to determine the optimum inclusion of NaOH necessary to buffer the acidity of dried distillers' grains with solubles (DDGS) and its effects on digestibility, ruminal metabolism, and metabolic acidosis in feedlot steers. Rumen cannulated Angus-crossed steers were blocked by BW (small: 555 ± 42 kg initial BW, n = 4; large: 703 ± 85 kg initial BW, n = 4) over four 21-d periods in a replicated 4 × 4 Latin square design. Steers were assigned to 1 of 4 dietary treatments: 1) 50% untreated DDGS, 2) 50% DDGS treated with 0.5% (DM basis) sodium hydroxide (NaOH), 3) 50% DDGS treated with 1.0% (DM basis) NaOH, and 4) 50% DDGS treated with 1.5% (DM basis) NaOH. The remainder of the diets, on a DM basis, was composed of 20% corn silage, 20% dry-rolled corn, and 10% supplement. Ruminal pH was not affected by treatments (P = 0.56) or by a treatment × time interaction (P = 0.15). In situ NDF and ruminal DM disappearance did not differ (P ≥ 0.49 and P ≥ 0.47, respectively) among treatments. Similar to in situ results, apparent total tract DM and NDF digestibility were not affected (P ≥ 0.33 and P ≥ 0.21, respectively) by increasing NaOH inclusion in the diets. Urinary pH increased (linear, P < 0.01) with increasing NaOH concentration in the diet. Blood pH was not affected (P ≥ 0.20), and blood total CO2 and partial pressure of CO2 were similar (P ≥ 0.56 and P ≥ 0.17, respectively) as NaOH increased in the diet. Increasing NaOH in the diet did not affect (P ≥ 0.21) ruminal concentrations of total VFA. There were no linear (P = 0.20) or quadratic (P = 0.20) effects of treatment on ruminal acetate concentrations, nor was there a treatment × time interaction (P = 0.22) for acetate. Furthermore, there were no effects (P ≥ 0.90) of NaOH inclusion on ruminal propionate concentration. However, there was a quadratic response (P = 0.01) of ruminal butyrate concentrations as NaOH inclusion increased in the diet; ruminal butyrate concentrations were greatest with the 0.5 and 1.0% NaOH treatments of DDGS. In the current study, feeding DDGS treated with NaOH did not increase fiber digestibility nor was it necessary to alleviate a possible metabolic acidosis. Alkali treatment of DDGS did not increase average ruminal pH or blood pH.